2004
DOI: 10.1182/blood-2004-02-0731
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms underlying iron transport deficiency in microcytic anemia

Abstract: A mutation of the iron transporter Nramp2 (DMT1, Slc11a2) causes microcytic anemia in mk mice and in Belgrade rats by impairing iron absorption in the duodenum and in erythroid cells, causing severe iron deficiency. Both mk and Belgrade animals display a glycine-to-arginine substitution at position 185 (G185R) in the fourth predicted transmembrane domain of Nramp2. To study the molecular basis for the loss of function of Nramp2(G185R), we established cell lines stably expressing extracellularly tagged versions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 23 publications
4
41
0
Order By: Relevance
“…Lanes 1, 5, and 9 are from mononuclear cells; lanes 2, 6, and 10 are from granulocytes; lanes 3, 7, and 11 are from platelets; lanes 4, 8, and 12 are from reticulocytes. al, 18 who demonstrated that when the DMT1 G185R mutant is stably expressed in cell lines it is abnormally glycosylated, less stable, and less active in metal transport. If present in detectable amounts in cells, the protein product of the exon 12-deleted mRNA does not appear to have a deleterious effect on iron absorption or utilization, as the patient's sister, who is a heterozygote and has a significant amount of the exon-deleted message, has no evidence of abnormal iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Lanes 1, 5, and 9 are from mononuclear cells; lanes 2, 6, and 10 are from granulocytes; lanes 3, 7, and 11 are from platelets; lanes 4, 8, and 12 are from reticulocytes. al, 18 who demonstrated that when the DMT1 G185R mutant is stably expressed in cell lines it is abnormally glycosylated, less stable, and less active in metal transport. If present in detectable amounts in cells, the protein product of the exon 12-deleted mRNA does not appear to have a deleterious effect on iron absorption or utilization, as the patient's sister, who is a heterozygote and has a significant amount of the exon-deleted message, has no evidence of abnormal iron metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Microcytic anemia (mk) mice and Belgrade (b) rats have systemic iron deficiency and anemia attributable to the same spontaneous missense mutation (G185R) in Slc11a2 (13,14). The mutation impairs both subcellular localization (15) and transport activity (16,17). We discovered that it also confers a novel calcium channel-like activity of uncertain importance (18).…”
Section: Introductionmentioning
confidence: 90%
“…6,12 The human DMT1 cDNA (non-IRE isoform, generous gift from Dr J. T. Prchal, Baylor College of Medicine, Houston, TX) was tagged by C-terminal HA epitope and inserted into the expression plasmid pcDNA3.1(Ϫ) (Invitrogen, Burlington, Canada). Site-directed mutagenesis was performed using the QuikChange and ExSite kits (Stratagene, La Jolla, CA) and allele-specific oligonucleotides: 5ЈGGCCAGTTTGTCATG-GACGGATTCCTGAACCTA3Ј, 5ЈTAGGTTCAGGAATCCGTCCATGA-CAAACTGGCC3Ј to create E399D DMT1; 5ЈCCCTTTGTAGATGTCCA-CAGCCAGTGT3Ј, 5ЈGGATTCCTGAACCTAAAGTGGTCACGCЈ3 to create DEL DMT1.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…3 DMT1 is an integral membrane protein composed of 12 predicted transmembrane domains (TM) and containing 2 putative glycosylation sites in an extracytoplasmic loop, membrane targeting motifs, and a consensus transport motif. 4,5 Recently, Touret et al 6 demonstrated that the G185R DMT1 mutant protein found in microcytic anemia (mk) mice 7 and the Belgrade (b) rats 8 is abnormally processed, less stable, and displays decreased transport activity. We previously reported a Czech female with severe hypochromic microcytic anemia and iron overload caused by a homozygous mutation in the DMT1 gene (1285G Ͼ C) that changes Glu 399 to Asp (E399D).…”
Section: Introductionmentioning
confidence: 99%